1998
DOI: 10.1063/1.475456
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact dissociative ionization of CO2: Measurements with a focusing time-of-flight mass spectrometer

Abstract: For reliable cross section data a focusing time-of-flight mass spectrometer has been presented which collects all the ions produced by the electron impact dissociative ionization of molecules. The focusing characteristic of the mass spectrometer generates the ions close to the axis and focuses the energetic ions back to the detector. By observing the deflection curves we can measure the cross sections conclusively. The complete collection allows one to extract the initial kinetic energy distribution of the ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 26 publications
8
37
0
Order By: Relevance
“…In this article, we report relative PICS σ r [X m+ ] for the formation of C + , O + , CO + , C 2+ , O 2+ and CO 2 2+ ions. This data is shown to be in excellent agreement with the existing PICS of Straub et al [14] and Tian and Vidal [16]. We then present precursor-specific relative PICS σ n [X m+ ], which, as shown by our recent studies of the electron ionization of C 2 H 2 [30] and N 2 O [31], quantify the contribution to the yield of a fragment ion from single (n = 1), double (n = 2) and triple (n = 3) ionization.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this article, we report relative PICS σ r [X m+ ] for the formation of C + , O + , CO + , C 2+ , O 2+ and CO 2 2+ ions. This data is shown to be in excellent agreement with the existing PICS of Straub et al [14] and Tian and Vidal [16]. We then present precursor-specific relative PICS σ n [X m+ ], which, as shown by our recent studies of the electron ionization of C 2 H 2 [30] and N 2 O [31], quantify the contribution to the yield of a fragment ion from single (n = 1), double (n = 2) and triple (n = 3) ionization.…”
Section: Introductionsupporting
confidence: 88%
“…In this way Straub et al [14] were able to demonstrate the complete collection of all ionic fragments, including those formed with considerable translational kinetic energy. Tian and Vidal [16] used a focusing time-of-flight mass spectrometer to measure PICS up to an electron energy of 300 eV and cross-sections for the formation of ion pairs up to 600 eV using a covariance mapping technique [15]. Comparison of these more recent determinations to the existing PICS data sets revealed some considerable discrepancies, particularly concerning the formation of the fragment ions C + and O + , for which the PICS values of Straub et al [14] and Tian and Vidal [16] are considerably larger than those measured in previous studies.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The experimental uncertainty is estimated to be ±10%. A similar measurement was performed by Tian and Vidal [49] in the energy range up to 300 eV. The two sets of results are in good agreement.…”
Section: Carbon Dioxide Moleculesupporting
confidence: 78%
“…Fox and Dalgarno (1979) concluded that in electron impact dissociation of CO 2 the mean energy released was ∼ 1 eV. Dissociative ionization, processes (12) and (14), are known to produce very energetic products (e.g., Locht and Davister 1995;Tian and Vidal 1998). The energetic ions and neutrals are mostly due to predissociation of electronically excited states of the ions.…”
Section: Photochemical-induced Escapementioning
confidence: 98%